Morphological Characterization of White Colored Grape Accession (Vitis vinifera L.) through Multivariate Approach under Indian Condition - Nale, R. D.; Somkuwar, R. G.; Kakade, P. B. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during October, 2022 to March, 2023 at ICAR-National Research Centre for Grapes, Pune, Maharashtra, India to characterize white colored grape genotype based on morphological qualitative traits and their relations. The morphological and fruit traits of 83 white coloured grape accession were evaluated. The grapevines were grown under standard recommended practices of irrigation, fertilization, and pest and disease control. The morphological quantitative traits such as bunch weight, bunch length, bunch width, berry length, berry diameter, berry thickness of skin, berry firmness of mesocarp, berry weight were in the following range 41.6–1456.5 g, 7.0–22.0 cm, 4.0–15.5 cm, 9.5–25.0 mm, 8.0–24.0 mm, 0.140–0.420, 25.0–88.0%, 55.0–316.0 g respectively, which indicated a wide level of diversity in the selected genotypes. Significant genotypic and phenotypic variation were observed among the studied accession for the measured characters. In addition, 4 types of berry flavor, 5 types of bunch shape and 6 types of different berry shape were observed. Multivariate analysis such as principal component analysis, cluster analysis was used for assessing the diversity of accession. The clustering dendrogram based on the obtained data showed two main cluster with several sub-clusters. The obtained data revealed high morphological variability within the studied collection of grapevine cultivars, which could be considered to characterize the large gene pool that contributes to the breeding process of grapes.